The Role of Rural Intelligence for the Development of the Medical Field - Kamolovna, Ravshanova Umida (European Journal of Life Safety and Stability (2660-9630), 2021)
The health-care development process is well underway. Serious initiatives are being taken, just as they are in industrialized countries, to attain the most inventive development. In particular, good initiatives to improve health care have defined the health prospects in the recent three years. The involvement of the country's enlighteners in the evolution of medicine is critical in this process. The removal of flaws in the medical system, as well as the participation of trained professionals in the activities of rural medical facilities, would help to grow the industry in rural areas. This article discusses the role and importance of rural intellectuals for the development of the medical field.